Tumor of orbit - Janicijevic-Petrovic,Mirjana A. (2014)
The cavernous hemangiomas are the most common intra orbital tumors found in adults of the middle age. Although histological benign, they can encroach on intra orbital or the adjacent structures (optic nerve) and be considered anatomically or positional malignant. We present a case report of orbital cavernous hemangioma of right orbit in young women after pregnancy, from Topola near Kragujevac (Central Serbia) with visual compromise and it's by trans-nasal endoscopic surgical management. Our patient was controlled and treated with the symptomatic therapy, topical therapy with artificial tears and surgical treatment. Our patient has optimal visual acuity of affected right eye after surgical treatment of orbital tumor. Surgical treatment of symptomatic orbital cavernous hemangioma is safe and effective, so that the cosmetic results are the important parameter to evaluate the clinical outcome.